On Kink-Dynamics of Stacked-Josephson Junctions - H. Susanto; T. P. P. Visser; S. A. van Gils (Institute for Research and Community Services (LPPM) ITB, 2002)
Dynamics of a fluxon in a stack of coupled long Josephson junctions is studied numericallv. Based on the numerical simulations, we show that the dependence of the propagation velocity c on the external bias current Î³ is determined by the ratio of the critical currents of thc two junctions J.